Same, but different - Drageset, Thomas (The University of Bergen, 2016)
The Nordic countries of Finland, Sweden and Norway is home to the Sámi people, an indigenous group that has in recent decades gone from political marginalization to empowerment. The strongest symbols of this political movement are the Sámi parliaments, political institutions that have been delegated power over Sámi cultural affairs. These parliaments are the main vehicle for maintaining and re-vitalizing the Sámi culture and language, both which have suffered greatly from assimilation policies of the Nordic states. However, the Sámi political sphere is currently marked by disunity among the three parliaments. As each has its own electorate, they all have their own electoral criteria as well, meaning there are three different interpretations on who is Sámi. How can this be? This thesis is a qualitative study on the three Sámi electoral criteria, with the research question why is there a difference in criteria among Sámi electorates in Norway, Sweden and Finland?" Through the method of process-tracing, the sequence of events that lead to the status quo is analyzed by looking at key events, documents, history and interviews. Debates are taking place within the Sámi political sphere between those who are excluded from enrolling in Sámi electorates, and those of the Sámi political establishment not recognizing them as Sámi. This debate is fueled by a perspective on identity held by some Sámi politicians known as essentialism, a belief that view re-vitalization of a culture impossible. Once a person has lost their Sámi- ness, it can never be regained. The findings and conclusion point towards an equifinal answer. The historical and external factors influencing the Sámi world has divided it, which means the Sámi parliaments each face different conditions and have acted in the interest of its own Sámi population. Master i Sammenliknende politikk SAMPOL350 MASV-SAPO